Misleading at birth congenital melanocytic nevus in a newborn with NF1. - Ferrante, M.R. (European Journal of Pediatric Dermatology, 2013)
Nevus anemicus is significantly more frequent in patients with peripheral neurofibromatosis (NF1). According to some Authors (2) nevus anemicus affects 51 % of patients with NF1 compared with 2% of controls. Congenital melanocytic nevus (CMN) can be scarcely pigmented at birth, and then be misdiagnosed as hypermelanic nevus, or even invisible (1). To the latter category belong those nevi more than one centimeter in diameter which become evident in the first six months of life and then do not grow further if not proportionally to the segment of skin on which they stay. These nevi become obvious after birth only due to increased production of melanin in response to an actinic or hormonal stimulus (1), certainly not due to a proliferation of epidermal melanocytes. The same phenomenon probably occurred in the nevus of our patient’s wrist.